Profiling of microbiome biodiversity and structure associated with the gastrointestinal tract of Pacific white shrimp (Penaeus vannamei) using high-throughput sequencing - MUHAMAD AMIN; LAILA MUSDALIFAH; MUHAMMAD WAHYUDIN LEWARU; ALIMUDDIN ALIMUDDIN; SAHRUL ALIM; MELISSA BEATA MARTIN (Society for Indonesian Biodiversity, 2024)
Abstract. Amin M, Musdalifah L, Lewaru MW, Alimuddin, Alim S, Martin MB. 2024. Profiling of microbiome biodiversity and structure associated with the gastrointestinal tract of Pacific white shrimp (Penaeus vannamei) using high-throughput sequencing. Biodiversitas 25: 1984-1992. The Pacific white shrimp (Penaeus vannamei) holds significant importance as an aquaculture commodity in Indonesia, where the government actively promotes the expansion of brackish water pond intensification and extensification. Despite its global cultured prominence, there remains a research gap regarding the biodiversity of the microbiome within the gastrointestinal tracts (GITs) of cultured P. vannamei and the implications of aquaculture practices on microbiota dynamics. This study focuses on investigating the diversity and structure of the GIT microbiome in P. vannamei from selective intensive aquaculture ponds in East Java, Indonesia. Sampling from three distinct intensive rearing ponds, shrimp GITs were meticulously dissected to analyze the bacterial composition using high-throughput sequencing. The microbial diversity within the gastrointestinal tracts of these shrimps from commercial intensive aquaculture farms was evaluated through 16S rRNA amplicon sequencing, targeting the V3-V4 region, and the utilization of Operational Taxonomic Units (OTUs) for bacterial categorization. The results revealed that the gastrointestinal tract of shrimp reared in an intensive aquaculture system was dominated by nine bacterial phyla, namely Proteobacteria (53.95%), followed by Actinobacteria (26.78%), Bacteroidetes (3.95%), Firmicutes (2.41%), Tenericutes (1.98%), Chloroflexi (1.22%), Verrucomicrobia (1.03%), Cyanobacteria (0.71%) and Planctomycetes (0.65%). High levels of microbial diversity were indicated by the diversity indices, reflecting both richness (Simpson's index) and evenness (Shannon index). The findings contribute to a deeper understanding of microbiota dynamics in aquaculture systems and underline the significance of preserving microbial diversity for sustainable shrimp production.